ANALISIS ANGGARAN RESPONSIF GENDER PADA APBD KABUPATEN SIDENRENG RAPPANG TAHUN 2019 - Ahmad Arif Syarif; Kurniawan Kurniawan; Amrizal Salida; Nur Hidayah (Lembaga Penelitian dan Publikasi Nobel Indonesia, 2023)
Gender mainstreaming is one of the important agendas for realizing a more inclusive national development. However, phenomena in the regions show that gender mainstreaming has not had a significant effect. One of the parameters that can be reviewed is based on local government budget allocations. This study aims to analyze the implementation of gender-responsive budgeting in local governments for the 2019 APBD period with a focus on research locations in Sidenreng Rappang Regency, especially the Office of Village Community Empowerment, Women and Child Protection. The research method used is qualitative with interactive data analysis by Miles and Huberman. The results of the study indicate that the regional government of Sidenreng Rappang Regency has not implemented gender mainstreaming in development because the results of the budget evaluation show that the budget at the Office of Village Community Empowerment, Women and Child Protection has not fulfilled the gender responsive budgeting aspect. This can serve as a reference for local governments to pay attention to gender in realizing inclusive development.